IMPROVING THE LEARNING OUTCOMES OF CLASS X TKJ SMK PERSIAPAN PEMATANG SIANTAR STUDENTS IN BASIC PROGRAMMING SUBJECTS USING A PROBLEM-BASED LEARNING MODEL - Naibaho, Holand (Edelweiss : Journal Of Innovation In Educational Research, 2025)
This study aims to improve the learning outcomes of students in class X TKJ SMK Persiapan Pematang Siantar in Basic Programming subject using Problem Based Learning learning model. The research was conducted considering the challenges in Basic Programming learning that affect student learning outcomes. The research method used is Classroom Action Research by collecting data through learning outcome tests, documentation and observation. The results showed that in the third cycle, the classical learning completeness rate reached 90%, which is included in the very high category. This shows that the use of Problem Based Learning model has significantly improved students' learning outcomes. In addition, students' responses to this learning model were also positive, with the emergence of a spirit of cooperation, activeness in learning, active participation in discussions, and clear delivery of ideas or opinions. Therefore, the Problem Based Learning learning model can be used as an effective alternative to improve student learning outcomes in Basic Programming subjects.